María Zambrano y su visión de América Latina. Lectura de cuatro ensayos - Valender, James (El Colegio de México, 2010)
This article examines the vision María Zambrano came to acquire of thefour Latin American countries she visited, in exile, between 1937 and 1953:Chile, Mexico, Puerto Rico and Cuba. Attention is paid to the interpretationshe offered of these countries in four essays written between 1937 and1959. Following the evolution in the philosopher’s thinking, analysis is madeof the E urocentric vision evident in the two earliest texts, as well as of theincreasing interest subsequently shown by her in all that was new to her inLatin America.